RELIGIOUSITY AND THEORY OF PLANNED BEHAVIOUR TOWARDS INTENTION TO GIVE INFAQ - Rifki Fajar Subekhi; Ririn Tri Ratnasari (Universitas Airlangga, 2017)
This study aims to determine the influence level of religiosity and Theory of Planned Behavior towards the intention to perform Infaq of traditional market Muslim traders. Data in this study is collected using questionnaires with sample research of 50 Muslim traders in the traditional market. Sampling techniques used are accidental sampling and purposive sampling. This research uses quantitative approach with multiple linear regression analysis. The results of this study indicate that religiosity level, behavior, Perceived Behavior Control, and subjective norms significantly influence the intention to perform infaq of traditional market Muslim traders. Suggestions for subsequent research are to increase the scope of research subjects to obtain more general information about related research, and to use other variables other than this research variable.Keywords: Religiosity, Theory of Planned Behavior, Intention to Give Infaq